Factors affecting perception of life insurance among Universiti Tunku Abdul Rahman Academics Staff in Perak Campus - Ho, Luin Yan; Koh, Ker Nee; Yeoh, Shirreena Yee Phing; Teoh, Jin Shuen; Yong, Wei Yeh (2020)
The objective of this research is to explore factors affecting perception of life insurance amongst UTAR academic staff in Perak campus. In addition, this is an exploratory study to examine whether socio-economic variables (income; education level; number of dependents) and perceived benefits, which are the independent variables, has association with the perception of life insurance, which is the dependent variable. In this study, 400 copies of survey questionnaires were handed out to UTAR academicians in Kampar and IBM SPSS Statistics 26 was used to analyse and interpret the collected data. The data was analysed using descriptive analysis, reliability test, normality test, Pearson Correlation Coefficient Analysis and Multiple Linear Regression. The results showed that perception of life insurance was affected by certain socio-economic variables and perceived benefits. Nonetheless, there were some limitations and recommendations in this study that will be further discussed in later chapters.